2021
DOI: 10.1093/nar/gkab099
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus inactivates the transcriptome and disrupts the chromatin architecture of its host cell in the first phase of lytic reactivation

Abstract: Epstein-Barr virus (EBV), a herpes virus also termed HHV 4 and the first identified human tumor virus, establishes a stable, long-term latent infection in human B cells, its preferred host. Upon induction of EBV’s lytic phase, the latently infected cells turn into a virus factory, a process that is governed by EBV. In the lytic, productive phase, all herpes viruses ensure the efficient induction of all lytic viral genes to produce progeny, but certain of these genes also repress the ensuing antiviral responses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 122 publications
4
34
0
Order By: Relevance
“…The mix was agitated on a mixing roller at 4 °C for 3 h. The cells were pelleted at 500 g at 4 °C for 10 min and washed with 1 ml ice-cold staining buffer (1% FBS and 2 mM EDTA in PBS). The anti-gp350 antibody (6G4) (Buschle et al, 2021) coupled to Alexa647 in 50 μl staining buffer (1:250 dilution) was added and the Elijah cells were incubated at 4 °C for 20 min. 1 ml staining buffer was added and the cells were washed and resuspended in 300 μl staining buffer and analyzed by flow cytometry (BD FACSCanto).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mix was agitated on a mixing roller at 4 °C for 3 h. The cells were pelleted at 500 g at 4 °C for 10 min and washed with 1 ml ice-cold staining buffer (1% FBS and 2 mM EDTA in PBS). The anti-gp350 antibody (6G4) (Buschle et al, 2021) coupled to Alexa647 in 50 μl staining buffer (1:250 dilution) was added and the Elijah cells were incubated at 4 °C for 20 min. 1 ml staining buffer was added and the cells were washed and resuspended in 300 μl staining buffer and analyzed by flow cytometry (BD FACSCanto).…”
Section: Methodsmentioning
confidence: 99%
“…BZLF1 is a homodimeric bZIP transcription and pioneer factor (Schaeffner et al, 2019) and binds two classes of BZLF1 (or ZEBRA) response elements (ZREs): CpG-free motifs resembling the consensus AP-1 site recognized by cellular bZIP proteins such as c-Jun/c-Fos (Farrell et al, 1989), and CpG-containing motifs that are selectively bound by BZLF1 upon cytosine methylation (Bhende et al, 2004; Dickerson et al, 2009; Bergbauer et al, 2010; Flower et al, 2011; Woellmer et al, 2012; Tillo et al, 2017; Buschle et al, 2021; Bernaudat et al, 2021). EBV’s virion DNA, which is unmethylated upon infection (Kalla et al, 2010), precludes the binding of BZLF1 to certain promoters of essential lytic viral genes in the pre-latent phase of infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Zta binds to and activates the expression of some cellular genes [35, 38–42]. Binding sites for Zta on the cellular cell genome in several B-cell lines have been identified [43, 44]. It was recently revealed that Zta binding to the human genome results in global changes to the architecture of cellular chromatin, opening some areas and making other areas inaccessible [44].…”
Section: Introductionmentioning
confidence: 99%
“…Binding sites for Zta on the cellular cell genome in several B-cell lines have been identified [43, 44]. It was recently revealed that Zta binding to the human genome results in global changes to the architecture of cellular chromatin, opening some areas and making other areas inaccessible [44]. The high number of Zta-binding sites has been postulated to contribute a buffer zone for Zta function; to prevent low levels of Zta initiating virus lytic cycle erroneously [44].…”
Section: Introductionmentioning
confidence: 99%